Food security strategies of an indigenous community in Veracruz, Mexico - Leyva-Trinidad, Doris Arianna; Pérez-Vázquez, Arturo; Newell, Gillian Elisabeth; García Albarado, J.Cruz; González Jácome, Alba (Ethnobiology and Conservation, 2021)
Amidst most indigenous groups in Mexico, traditional knowledge still prevails which constitutes local strategies that address the issue of food insecurity. This study aims to analyze the body of Traditional Agroecological Knowledge (TAK) of Nahuatl indigenous community of Ocotal Texizapan, Tatahuicapan, Veracruz, to understand the strategies practiced to achieve food security. Participatory observation and semi-structured and in-depth interviews at the household level (n = 20 families) revealed that Traditional Agroecological Knowledge and local life strategies are linked to the “milpa” (traditional agroecosystem), home gardening, gathering, hunting and fishing activities which are key components to achieve food security at the family level. Rain-fed and "tapachole" (residual humidity) milpa, based on sowing maize intercropped with several crops, are closely-related to direct empirical knowledge, the rational use of available natural resources, family labour, and local knowledge. Currently, changes in land use and the use of agrochemicals are increasing in the study community and depleting biodiversity affecting food security at the family level: a situation that endorses the importance of traditional agriculture (milpa), backyard livestock (hens, ducks, pigs) together with gathering, hunting and fishing among the Nahuatl families.